2021
DOI: 10.3390/molecules26102965
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Topological Insulators in Real Space

Abstract: A real space understanding of the Su–Schrieffer–Heeger model of polyacetylene is introduced thanks to delocalization indices defined within the quantum theory of atoms in molecules. This approach enables to go beyond the analysis of electron localization usually enabled by topological insulator indices—such as IPR—enabling to differentiate between trivial and topological insulator phases. The approach is based on analyzing the electron delocalization between second neighbors, thus highlighting the relevance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, recent studies have shown that real-space descriptors can characterize the topology of a system. [55][56][57] In particular, the sublattice polarization can characterize the topology of SSH-edge states, predicting the topological phase of the system regardless of bulk. 57 As we have seen previously, for low energies, AGNR superlattices under strain behave like an SSH system, giving us the possibility to describe the topological states by means of the sublattice polarization.…”
Section: Sublattice Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, recent studies have shown that real-space descriptors can characterize the topology of a system. [55][56][57] In particular, the sublattice polarization can characterize the topology of SSH-edge states, predicting the topological phase of the system regardless of bulk. 57 As we have seen previously, for low energies, AGNR superlattices under strain behave like an SSH system, giving us the possibility to describe the topological states by means of the sublattice polarization.…”
Section: Sublattice Polarizationmentioning
confidence: 99%
“…[55][56][57] In particular, the sublattice polarization can characterize the topology of SSH-edge states, predicting the topological phase of the system regardless of bulk. 57 As we have seen previously, for low energies, AGNR superlattices under strain behave like an SSH system, giving us the possibility to describe the topological states by means of the sublattice polarization. Indeed, the electrical transport in AGNR superlattices can be described by the degree of sublattice polarization of its topological-like modes.…”
Section: Sublattice Polarizationmentioning
confidence: 99%